Surgical provider-reported reasons for utilization of the World Health Organization's Surgical Safety Checklist at a tertiary hospital in Ghana. - Eyram Cyril Bansah; Kekeli Kodjo Adanu; David Adedia; Adolphina Addoley Addo-Lartey (Public Library of Science (PLoS), 2023)
Despite the established positive benefits, LMICs' adoption of the WHO Surgical Safety Checklist (SSC) is inadequate, with as little as 20% use. This study assessed the utilization and beliefs that drive the non-utilization of the WHO SSC among surgical providers at Korle Bu Teaching Hospital (KBTH) in Accra, Ghana. A cross-sectional study was conducted among 186 surgical providers at the KBTH in Ghana. Data collected included the category of personnel, awareness of the SSC, training received, previously identified barriers, and staff perceptions. Utilization and drivers associated with non-utilization of the SSC were assessed using bivariate log-binomial regression. Out of 190 surgical professionals invited, 186 gave their consent and participated in the survey, giving a response rate of 97.9%. Respondents comprised 69 (37%) surgeons, 66 (36%) anesthetists, and 51 (27%) nurses. Only 30.4% of surgical professionals always use the SSC, as advised by WHO. The majority (67.7%) of surgical professionals had received no formal training on using the WHO SSC. The proportion was highest among surgeons (81.2%) compared to anesthetists (66.7%) and nurses (51%). Surgeons were perceived by other professionals to be the least supportive of checklist use (87.6%), in contrast to nurses (96.1%) and anesthetists (93.9%). Significant drivers associated with checklist usage among surgical professionals included the SSC taking too long to complete, poor communication between anesthetist and surgeon, checklist not covering all perioperative risks, difficulty finding a coordinator, poor attitude of team members toward questions, surgical specialty/unit and training status of professionals. The checklist was always used by only a small (30%) proportion of surgical professionals at the KBTH. Improving checklist use will necessitate its careful application to all surgical operations and a cycle of periodic training that includes context-specific adjustments, checklist auditing, and feedback from local coordinators.